PERSEPSI PASIEN RAWAT JALAN TERHADAP PELAYANAN KESEHATAN DI RSUD ROKAN HULU KECAMATAN RAMBAH KABUPATEN ROKAN HULU - Giwang, Yohana Retno Puspo; ", Indrawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This study titled "Perception Outpatient Against Health Care in the Hospital District of Rambah upstream Rokan Rokan Hulu". Researchers are interested in this theme because of problems about services often constrained in upstream Rokan Hospital. The purpose of this study was to determine how perceptions of ambulatory patients to medical services in hospitals rokan upstream and the factors that influence patients' perceptions of the care in hospitals rokan upstream. This type of research in this thesis is quantitative descriptive which describe the results of research and analysis in order to obtain the results and then conclude. The unit of analysis in this study were outpatients who had previously been determined researcher. Data collection techniques in this study is the observation, questionnaire and documentation. From the results of research in the field that the perception of outpatient visits to health services on the overall dimensions of service is good, is seen from the perception outpatient berpersepsi mostly positive, although there are some that berpersepsi masi negatively affect hospital services Rokan upstream. Then their influence on the perception of the patient's experience, from mood was not all that good mood berpersepsi patients are good also for patients berpersepsi good depending on the services they get, then the effect on the patient's knowledge. of facilities that are not all good perception of the comfort of the waiting room amenities are met.Keywords: Perception, Health Services, Hospital